التفريق بين الزوجين للعيوب الجنسية - القضاة، أحمد مصطفى علي (كلية الدراسات الاسلامية والعربية, 2005)
The research deals with Jurisprudence laws which are related to the separa¬tion between the husband and the wife because of sexual defects. It also deals with the laws which allow such a separation, those that limit it, the con¬ditions required to prove it, and those who carry out the separation and its procedures. It also deals with different types of separation, the dissolving of the divorce, the treatment of sexual defects, the brideĺs dowry, the periods which follow the divorce, and the renewing of the marriage contract. ???
يتناول هذا البحث الأحكام الفقهية المتعلقة بالتفريق بين الزوجين للعيوب الجنسية، سواء القديمة منها أو المعاصرة، من حيث الحكم الشرعي للتفريق بسبب العيوب الجنسية، والعيوب المجيزة للتفريق وهل هي محصورة أم لا؟ ومن يثبت له هذا الخيار؟ ومن يتولى التفريق وإجراءاته والشروط الواجب توافرها لثبوته، كما يوضح البحث نوع الفرقة الواقعة بالعيب... فسخ أم طلاق؟ وأثر معالجة العيب الجنسي على التفريق، وحكم المهر والعدة وإعادة العقد.
Keywords: إعادة العقد -- الأحكام الفقهية -- التفريق بين الزوجين -- العيوب الجنسية -- حكم المهر -- العدة